Stock market multiples in the valuation of unlisted agrifood companies - Raúl Vidal García; Javier Ribal Sanchis; Ana Blasco Ruiz (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
Stock price determination is one of the main issues involved in the acquisition of companies. The transparency and high volume of the stock market make it possible to ascertain valuation multiples. In the case of privately-held agrifood companies, valuation multiples are scarce and barely representative. This paper focuses on answering whether listed stock valuation multiples of the agrifood industry can be useful for the purposes of valuing unlisted small and medium-sized companies. A study into Spanish unlisted agribusinesses is designed for several samples and accounting years. By means of a discounted cash flow model combined with bootstrap techniques, the empirical distribution of the unlisted multiples is obtained for three growth hypotheses. The results show that the stock market P/E should not be used in the valuation process of unlisted agrifood companies, whereas the stock market EV/EBITDA may be used in the valuation process of unlisted small and medium-sized agrifood companies that consistently obtain positive cash flows.
Keywords: G12; G34; M41; Q14; 330; SMEs; bootstrap; food industry; valuation multiples